Plasma Lipoxin A(4) and Resolvin D1 are Not Associated with Reduced Adenoma Risk in a Randomized Trial of Aspirin to Prevent Colon Adenomas - Fedirko, Veronika (Mol Carcinog, 2017)
Inflammation plays a major role in colon carcinogenesis. Endogenously produced specialized proresolving lipid mediators (SPMs) play a central role in inflammation and tissue homeostasis, and have been implicated in carcinogenesis. We studied the associations of plasma levels of two SPMs [lipoxin A(4) (LXA(4)) and resolvin D1(RvD1)] with risk for recurrent adenoma. In this pilot study, we used data and biosamples from an adenoma chemoprevention study investigating the effects of aspirin and/or folic acid on the occurrence of colorectal adenomas. In the parent study, 1,121 participants with a recent adenoma were randomized to study agents to be taken until the next surveillance colonoscopy about 3 years later. In this pilot study, LXA(4) and RvD1 from samples taken near the end of study treatment were measured in a randomly selected sub-set of 200 participants. Commercially available ELISA kits to assay the analytes were validated using a metabololipidomic LC-MS/MS assay. Poisson regression with a robust error variance was used to calculate risk ratios and 95% confidence intervals. Plasma LXA(4) and RvD1 were not associated with the risk of adenoma occurrence. LXA(4) at the end of study follow-up was 32% (P=0.01) proportionately higher in women compared to men. A similar non-significant trend towards higher levels among women was observed for RvD1. Our preliminary findings provided no evidence that plasma LXA(4) or RvD1 are associated with reduced risk of colorectal adenoma occurrence, but suggest LXA(4) may differ among men and women. Future studies focusing on SPM’s local effects and levels in the colon are needed.